What do Italian adolescents think about the ‘Blue Whale’ Internet Game? - Massaro, Davide; Castelli, Ilaria; Florio, Eleonora; Marchetti, Antonella (Università della Svizzera italiana, 2018)
The Internet game Blue Whale Suicide Challenge (BWSC) represents a potential new at-risk behaviour for psychologically vulnerable teenagers and young adults worldwide. The game is managed by an administrator, that starts by motivating individuals towards minor and relatively safe self-infliction challenges, and then gradually escalates to more dangerous challenges up to arrive to the final challenge, represented by suicide. The BWSC has had great impact on Italian media, raising questions and concerns in parents, educators and teachers. Therefore, as a contribution to the systematic reflection about the BWSC, we thought it would be important to understand adolescents’ perspectives about the phenomenon and to analyse vulnerability situations. The goals of this study are to understand adolescents’ knowledge about BWSC at descriptive level and to explore the relationships among problematic Internet use and psycho-social vulnerability. To reach these goals we carried out an online survey including: (1) Socio-demographic data; (2) Ad hoc questions about adolescents’ knowledge of BWSC game; (3) The Generalized Problematic Internet Use Scale 2 (GPIUS2; Caplan, 2010; Fioravanti, Primi, & Casale, 2013), 15 items rated on an eight-point Likert scale, assessing four dimensions: (posi) preference for online interpersonal interactions; motivation to use Internet to alleviate distressing feelings (mood regulation); inability to control or regulate one’s online behaviour (deficient self-regulation) and personal, social, and professional problems resulting from Internet use (negative outcomes); (4) The Toronto Alexithy- mia Scale (TAS-20; Bressi et al., 1996; Taylor et al., 1991), 20 items rated on a five-point Likert scale, assessing the different aspects of alexithymia: difficulty in identifying feelings, difficulty in expressing feelings, and externally oriented thinking; (5) The Depression-Anxiety Stress Scale (DASS-21; Bottesi et al., 2015; Lovibond & Lovibond, 1995), 21 items evaluating depression - lack of ...